Finite element parametric study of the behavior of segmental block reinforced-soil retaining walls. Issue 3 (1st June 2003) - Ling, H. I.; Leshchinsky, D.
Abstract : Geosynthetic-reinforced-soil retaining walls with modular-block (segmental) facing have gained wide popularity because of their satisfactory performance and aesthetic appearance. A better understanding of the deformation of this wall system requires an analytical tool that is capable of considering the properties of soils, geosynthetic reinforcement, and soil–structure interactions in a realistic manner. In this paper, a validated finite element procedure was used with a hyperbolic soil model for conducting a series of analysis under working-stress conditions. The effects of the length, spacing and stiffness of reinforcement, the width, interaction and connection strength of the modular block, and the backfill and foundation soil properties were investigated. The deformation and lateral stress at the wall face, vertical stress along the base of the wall and the strains developed in the geosynthetic reinforcement are discussed. All design parameters were found to affect the wall performance with a certain degree of sensitivity.